THE EFFECT OF COOPERATIVE LEARNING METHOD IN IMPROVING STUDENTS' ISLAMIC RELIGIOUS EDUCATION LEARNING OUTCOMES AT MAN 2 KOTA PALU - Nufitasari, Intan; Rustina; Patanggu, Irawanhadi (Al-Tawjih: Jurnal Pendidikan Islam, 2025)
This research discussed the importance of employing effective learning methods to improve students' learning outcomes in Islamic Religious Education (PAI). The objective of this research is to determine the effect of the cooperative learning method on improving students' learning outcomes at MAN 2 Kota Palu.This research used a quantitative approach with a nonequivalent control group design. The research subjects consist of two groups: the experimental class, which received the cooperative learning method, and the control class, which used the conventional method. Data were collected through an initial test (pretest) and a final test (posttest). Data analysis used the Wilcoxon test to examine differences before and after the treatment and the Mann-Whitney U test to compare learning outcomes between the two groups. The research results indicated a difference between the students' pretest and posttest scores, with a significance level of 0.007 < 0.05. However, the Mann-Whitney U test results show a p-value greater than 0.05, indicating no significant difference in learning outcomes between the experimental and control classes. The conclusion of this research is that the cooperative learning method has not yet provided a significant effect on improving students' learning outcomes compared to the conventional method. Nevertheless, this method still has potential to enhance students' engagement, collaboration, and social skills in the learning process.